Influence of Cardiorespiratory Fitness on PPARG mRNA Expression Using Monozygotic Twin Case Control - Marcos Roberto Queiroga; Ricardo Augusto Barbieri; Sandra Aires Ferreira; André Ducati Luchessi; Rosario Dominguez Crespo Hirata; Mario Hiroyuki Hirata; Eduardo Kokubun (Journal of Diabetes Research)
The influence of cardiorespiratory fitness (VO2max) on anthropometric variables and PPARG mRNA expression was investigated. Monozygotic twin pairs aged 11–18 years were grouped into discordant (D) and concordant (C) high and low VO2max groups. VO2max was determined by progressive maximal exercise test on treadmill with gas exchange analysis. Body mass (BM), BMI, waist circumference (WC), triceps (TR), and subscapular (SB) skinfold thicknesses were measured. Twins from the discordant group had differences in VO2max values (D-high = 45.9±10.0 versus D-low = 32.4±10.6 mL·kg−1·min−1, P=0.025), while no differences were found in the concordant group (C-high = 42.4±9.2 versus C-low = 38.8±9.8 mL·kg−1·min−1, P=0.952). In discordant group, VO2max was negatively correlated with TR + SB (r=-0.540, P=0.021) and positively correlated with PPARG expression in leukocytes (r=0.952, P=0.001). Moreover, PPARG expression was directly correlated with BM (r=0.714, P=0.047) and height (r=0.762, P=0.028). In concordant twins, VO2max was inversely correlated with BM (r=-0.290, P=0.027), BMI (r=-0.472, P=0.001), WC (r=-0.426, P=0.001), and TR + SB (r=-0.739, P=0.001). Twins D-high had 1.78-fold greater PPARG expression when compared with twins D-low (P=0.048). In conclusion, the cardiorespiratory fitness may modulate PPARG expression in childhood and adolescence, independently of the genetic background.